2019
DOI: 10.1037/tps0000195
|View full text |Cite
|
Sign up to set email alerts
|

Legal professionals’ perceptions of juvenile engagement in the plea process.

Abstract: Criminal and juvenile court cases are often resolved through plea bargaining. Although the courts have decreed that plea decisions must be made knowingly, intelligently, and voluntarily, little is known about legal professionals' broader perceptions of defendants' engagement in the plea process; in other words, professionals' views of whether defendants understand, attend to, and participate in the plea process. Perceptions of juvenile defendants are of particular interest, given that they are especially vulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Our findings here, along with those from prior studies (e.g., Redlich & Summers, 2012; Woestehoff et al, 2019; Zottoli & Daftary-Kapur, 2019), raise important questions about defendants’ participation and engagement in the plea process. Our descriptive data on the flow and characteristics of, and defendant participation in, guilty plea hearings for juvenile and adult court defendants paint a less than rosy picture.…”
Section: Discussionsupporting
confidence: 70%
“…Our findings here, along with those from prior studies (e.g., Redlich & Summers, 2012; Woestehoff et al, 2019; Zottoli & Daftary-Kapur, 2019), raise important questions about defendants’ participation and engagement in the plea process. Our descriptive data on the flow and characteristics of, and defendant participation in, guilty plea hearings for juvenile and adult court defendants paint a less than rosy picture.…”
Section: Discussionsupporting
confidence: 70%
“…Age was proposed to shape participation in that it influences capacity for choice. Contextual antecedents of participation included initiatives that influence the physical, attitudinal, and relational environment [ 33 , 42 , 43 ]; information provided [ 66 ]; and peer modelling, family processes, socioeconomic factors, cultural practices, and governance structures [ 67 , 68 ]. These broad-ranging antecedents provide information about how contexts might be shaped or influenced to support participation.…”
Section: Core Difficulties With the Definition And Operationalizatmentioning
confidence: 99%
“…Consequences of a lack of participation were reported to include deprivation, social injustice, limited wellbeing, lack of dignity, loss of rights [ 47 , 66 ], and a lack of involvement leading to lack of attendance at work or low productivity [ 33 ]. A lack of participation can lead to a lack of contribution to building social capital by particular groups in society.…”
Section: Core Difficulties With the Definition And Operationalizatmentioning
confidence: 99%
“…As discussed earlier it is not uncommon for conflicts of interest to arise; future research should explore how attorneys navigate these conflicts with parents while prioritizing their client's expressed interests. Additionally, recent work has shown that legal actors' perspectives of juvenile engagement within the plea bargain process vary (Woestehoff et al, 2019). They found that defense attorneys often evaluated juvenile clients as less engaged than prosecutors and judges did.…”
Section: Implications For Research and Practicementioning
confidence: 99%